Stannous fluoride forms aggregates between outer and inner membranes leading to membrane rupture of Porphyromonas gingivalis and Prevotella pallens - Xie, Sancai; Iberi, Vighter; Boissy, Ying; Tansky, Cheryl S.; Huggins, Tom; Ramji, Niranjan; Biesbrock, Aaron R. (Frontiers in Oral Health, 2024)
Objective Stannous has been shown to bind to free lipopolysaccharides, thus preventing them from binding to TLR receptors. This study was undertaken to determine the histomorphological mechanism of stannous binding to anaerobic bacteria. Methods Two bacteria associated with gingivitis and advanced periodontal disease, Porphyromonas gingivalis (P. gingivalis) and Prevotella pallens (P. pallens), were cultured in 25–1,000 μM of stannous fluoride and stannous chloride for 48 h. The growth rate was estimated using absorbance OD600. Bacterial cells were then fixed and processed for transmission electron microscopy (TEM) analysis. Results Stannous fluoride inhibited proliferation of both P. gingivalis and P. pallens in a dose-dependent manner. There was a statistically significant suppression of the growth curve starting at 100 μM for P. pallens (P = 0.050) and 200 μM for P. gingivalis (P = 0.039). TEM analysis revealed a thick layer of polysaccharides (19.8 nm) in P. gingivalis. The outer and inner membranes were clearly visible with low electron densities in both bacteria. Stannous diffused into bacterial membranes and formed precipitates in the areas spanning outer and inner membranes and below inner membranes. Precipitates varied in size ranging from 46.4 to 84.5 nm in length, and 18.4 to 35.9 nm in width. The membranes were disintegrated in the region where stannous formed precipitates. Cytosolic contents were leaked out, and in several cases, small vesicles were formed. Stannous precipitates were more abundant in numbers and larger in size in bacteria treated with high concentrations (100–300 μM) than in low concentrations (25–50 μM) of stannous fluoride. Furthermore, most of the bacteria were disintegrated in the groups treated with 100–300 μM stannous fluoride. At low concentrations (25 μM), stannous fluoride formed complexes primarily around outer membranes, to which lipopolysaccharides are anchored. Stannous chloride results showed similar trends, but it was less potent than stannous fluoride. Conclusion Stannous fluoride can penetrate bacteria, bind to the constituents of the membrane and form precipitates between outer and inner membranes and beneath inner membranes. These large precipitates damaged the integrity of membranes and allowed cytosolic contents to be leaked out. Stannous complexes formed at the outer membranes, even at low concentrations (25 μM).